O uso de artefatos históricos nas aulas de matemática: uma análise em anais de eventos científicos - Nascimento, Maria de Fátima Gomes do (2018)
This study aimed to investigate the use of Historical Artifacts, based on the annals of the National Seminar on Mathematical History and the National Meeting on Mathematical Education. This is a qualitative-descriptive documentary research. The theoretical basis was based on the works of Mendes (2001), Oliveira (2009, 2017), Feliciano (2008), Brazil (1998, 2006), among others. As results it was verified that there are still few works published in annals of events that present Historical Artifacts through the history of mathematics. Considering that the Historical Artifacts open up a range of possibilities both for the work with the mathematical contents and for the interconnection of these contents with other areas of knowledge, thus allowing the students to be able to visualize some sense the study of Mathematics we conclude that it is further research on this topic is needed.